A life controlled by the current: rheotaxis behavior of the river prawn Macrobrachium tenellum (Decapoda: Palaemonidae) - Peña-Almaraz, Omar Alejandro (2024)
Introduction: The currents of streams and rivers are natural signals that influence the migrations in the life cycle of amphidromous shrimp. Objective: To evaluate the rheotaxis behavior in juveniles and adults of Macrobrachium tenellum, in relation to their response capacity to different water currentspeeds in a closed-loop experimental system. Methods: A PVC pipe system was used, with a tub for water recirculation and a backwater placed in the middle of the system. Water flows of 10-30 cm/s were tested to establish the experimental conditions. Rheotaxis behavior without backwater (SR) and with backwater (CR) was evaluated; three water flows were tested: FI, 14 cm/s; FII, 18.7 cm/s; and FIII, 22.1 cm/s, and a control FC flow, 0 cm/s, with 40 juveniles, 40 females and 40 males per flow. Three main behaviors were identified: positive rheotaxis, negative rheotaxis, and no reaction. Results: For both SR and CR, water flows stimulate positive rheotaxis and the behavioral response is different depending on the speed of the water flow and whether they are juveniles, females, or males. In CR there was a greater response of the prawns to continue swimming against the current when they entered the pool. At a straight angle, the constant flow of water greater than 23.2 cm/s makes it difficult for this species to swim against the current Conclusions: The positive rheotaxis response was the most prevalent in juveniles, females, and males of M. tenellum.